Japanese propaganda in war-time Malaya: Main issues in Malai Shinpo and Syonan Shinbun - Fathil, Fauziah; Fathil, Fathiah (Faculty of Communication and Media Studies, UiTM, 2017)
Propaganda and war are often linked up together that they have become essentially inseparable. While there are different kinds of propaganda to serve different purposes, propaganda during war or war propaganda is the most noteworthy that not only has it become a common phenomenon during events of conflict in human history but serves as the underlying reason for the term ‘propaganda’, as perceived by many, to bear negative connotations. As in other countries that experienced war, Malaya during Japanese occupation from 1941-45 saw vigorous war propaganda carried out by the invading authorities. This paper aims to highlight such effort on the part of Japanese administration in their attempt to win the support of Malayans through the medium of press or newspapers. In doing so, two notable newspapers were selected namely Malai Shinpo and Syonan Shinbun. Not only did they last longer and more regular during the war years than others, but more importantly, they served as official propaganda tools for the Japanese war campaign in Malaya. As instruments of propaganda, certain distinctive patterns or trends can be seen in the contents of the newspapers with the aim none other than to enhance the Japanese rule. Using the method of qualitative and library research, the findings of this paper will not only further enrich knowledge on the history of the Japanese occupation of Malaya, but also provide more information on the development of press or newspapers in the first half twentieth century Malaya, a topic which has yet to be extensively explored.